2007
DOI: 10.2478/s11696-007-0033-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of addition of ameliorative materials on the distribution of As, Cd, Pb, and Zn in extractable soil fractions

Abstract: The effects of lime, limestone, and zeolite addition on the availability of As, Cd, Pb, and Zn in three contaminated soils were investigated in a pot experiment after four vegetation periods of spring wheat, spring barley, and oat. The results showed different responses of extractable element portions to soil amendment when 0.01 mol dm−3 aqueous CaCl2 was applied as a soil extraction agent. Substantial differences were evident among the investigated elements as well as among the individual soil treatments. Exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In the 0-10 cm layer, an obvious effect of pH on the concentration of plant-available Zn was detected while no effect of liming was observed with Pb. These results were in accordance with other authors (Chowdhury et al 1997;Huang et al 2005;Száková et al 2007).…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…In the 0-10 cm layer, an obvious effect of pH on the concentration of plant-available Zn was detected while no effect of liming was observed with Pb. These results were in accordance with other authors (Chowdhury et al 1997;Huang et al 2005;Száková et al 2007).…”
Section: Discussionsupporting
confidence: 96%
“…In the RGE, the effect of As present in basic slag combined with the enhanced mobility of As caused by the addition of phosphate fertilisers was apparent. Huang et al (2005) reported no significant changes in As mobility in limed soil, whereas in experiments published by Száková et al (2007) the mobile portion of As in limed soil tended to increase as in the RGE. There are many contradicting results that make it difficult to give exact explanations for these differences.…”
Section: Discussionmentioning
confidence: 74%